Attitudes towards insect-based foods: the Polish consumer perspective - Pachołek, Bogdan; Bartkowiak, Paweł; Michalak, Szymon; Stachowiak-Krzyżan , Magda (Economics and Environment, 2025)
The aim of the article was to assess Polish consumers’ attitudes towards insect-based products according to respondents’ gender, age, place of residence, level of education and material situation. The study used a quantitative approach based on data from an online survey conducted in 2023 with 631 Polish respondents. The survey included 15 variables measured on a five-point scale describing consumers' attitudes towards insect-based food. Descriptive statistics and exploratory factor analysis were used to identify the key components that define consumer attitudes and behaviours towards insect-based food. The results suggest that Polish consumers generally lack sufficient information on this category of products and are not inclined to spend time looking for it. Instead, they show a certain level of reluctance towards this type of food. Consumers do not perceive it as healthy, safe or nutritious. The research findings suggest that the adoption of insect-based food among Polish consumers may be problematic.